2017
DOI: 10.3389/fpubh.2017.00140
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hominis and Mycoplasma genitalium in the Vaginal Microbiota and Persistent High-Risk Human Papillomavirus Infection

Abstract: BackgroundRecent studies have suggested that the vaginal microenvironment plays a role in persistence of high-risk human papillomavirus (hrHPV) infection and thus cervical carcinogenesis. Furthermore, it has been shown that some mycoplasmas are efficient methylators and may facilitate carcinogenesis through methylation of hrHPV and cervical somatic cells. We examined associations between prevalence and persistence of Mycoplasma spp. in the vaginal microbiota, and prevalent as well as persistent hrHPV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 47 publications
(49 reference statements)
2
58
0
Order By: Relevance
“…The LEfSe analysis in the present study also confirmed enrichment of the genus Haemophilus and family Mycoplasmataceae in HPV-persistence women. The results for Mycoplasmataceae are in agreement with the finding of Abedamowo et al ., that Mycoplasma hominis in cervical microbiota is significantly associated with hr-HPV infection 16 . It has also been reported that a few Mycoplasma species are efficient methylators and can promote cervical carcinogenesis through methylation of hr-HPV and cervical somatic cells 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEfSe analysis in the present study also confirmed enrichment of the genus Haemophilus and family Mycoplasmataceae in HPV-persistence women. The results for Mycoplasmataceae are in agreement with the finding of Abedamowo et al ., that Mycoplasma hominis in cervical microbiota is significantly associated with hr-HPV infection 16 . It has also been reported that a few Mycoplasma species are efficient methylators and can promote cervical carcinogenesis through methylation of hr-HPV and cervical somatic cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The results for Mycoplasmataceae are in agreement with the finding of Abedamowo et al ., that Mycoplasma hominis in cervical microbiota is significantly associated with hr-HPV infection 16 . It has also been reported that a few Mycoplasma species are efficient methylators and can promote cervical carcinogenesis through methylation of hr-HPV and cervical somatic cells 16 . One of the previous cervical microbiota studies (16-weeks samples) conducted by Brotman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies, including a total of 12.204 patients, have been published in the literature with regard to the association between vaginal microbiota and HPV infection ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In 194 Nigerian women tested for high-risk human papillomavirus (hrHPV), a significant association with Mycoplasma hominis (M. hominis) was observed with an OR of 8.78 (95% Confidence Interval, 1.49-51.6, P = 0.01) and human immunodeficiency virus (HIV) positive females had a three-fold increase in OR in the presence of persistent hrHPV infection [187].…”
Section: Mycoplasmmentioning
confidence: 99%